The PROBLEM BASED LEARNING AND PROJECT BASED LEARNING IN RELATION TO CREATIVITY AND CRITICAL THINKING TOWARDS THE COMPETENCE OF VOCATIONAL EDUCATION STUDENTS - Dimas Arya Soeadyfa Fridyatama; Farid Baskoro; Meita Maharani (Jurnal Penelitian, 2025)
Problem-Based Learning (PBL) and Project-Based Learning (PjBL) are instructional models that play a crucial role in developing students' skills and competencies. The implementation of PBL and PjBL has an impact on enhancing students' creativity and critical thinking abilities in achieving competencies that are relevant to the demands of the current era. This research aims to examine the relationship between creativity, critical thinking, and students' competencies in the field of vocational education through problem-based and project-based learning approaches. The research methodology employed is a qualitative approach with an exploratory study design. The research participants consist of 200 students majoring in Air Traffic Control in Vocational Aviation Education, comprising 70 final-year students, 70 intermediate-level students, and 60 entry-level students from aviation colleges with competencies in Aerodrome Flight Information Services (AFIS). The research instrument utilized is a questionnaire of the Measures of Typical Performance (MTP) type to gather student responses. The statistical analysis results using SEM-PLS reveal an R-Square value of 0.953 or 95%, indicating a significant relationship between creativity, critical thinking, and students' competencies in the field of vocational education.